Smartphones and their use by teenagers and young adults - differences and similarities: A case study - Papalexopoulou, Konstantina; Psiachou, Konstantina (Homo Virtualis, 2018)
Advances in Information and Communication Technologies (ICTs) promoted social media and social networking sites as an integral part of the psychosocial reality of modern people, especially the younger ones. This is an unprecedented form of networked lived experience, where people are always connected and always available through various social media platforms. How do teenagers who grew up in a given technosocial context perceive modern reality as compared to the slightly older young adults who, nevertheless, experienced a slightly different technosocial environment as children? Is there a kind of “generation gap” even among people who differ marginally in their age? In this case study we attempt a preliminary investigation of the field by conducting four ethnographic interviews with two teenagers and two young adults. Preliminary qualitative analysis showed increased use of smartphones by the participants, mostly for communication reasons and mainly through online services and social media. Both teenagers and young adults emphasize the effects of technology on everyday life and point out the potential risks, even though they remain optimistic for the future impact on human life. Our findings indicate that there are differences between the two age groups as regards their preferences for specific social media platforms and social apps.